MENGKRITISI POLA PENGAJARAN ORANG TUA BAGI ANAK DI ERA INDUSTRI 4.0 BERDASARKAN PERSPEKTIF TEOLOGI KRISTEN - Marten Toding Kayang; Silpa Marisu; Jelni , Jelni; Irawanti K. T.; Izebel Poppy B. Yonatan (CV. Adiba Aisha Amira, 2024)
This research aims to examine and criticize the teaching patterns of parents towards their children in the era of Industry 4.0, referring to the perspective of Christian theology. By using a qualitative approach, the study analyzes the impact of technological changes and the work environment on parental teaching practices. The theological implications of the research findings highlight the challenges and opportunities parents face in balancing the use of technology with Christian values in shaping the character of their children. The study's results are expected to provide a profound insight into how Christian theology can guide parents in forming relevant and meaningful teaching patterns amidst the dynamics of modern societal changes.